An overview of the mental health system in Gaza: an assessment using the World Health Organization’s Assessment Instrument for Mental Health Systems (WHO-AIMS) - Saymah, Dyaa; Tait, Lynda; Michail, Maria (BioMed Central, 2015)
Background: Mental health system reform is urgently needed in Gaza to respond to increasing mental health consequences of conflict. Evidence from mental health systems research is needed to inform decision-making. We aimed to provide new knowledge on current mental health policy and legislation, and services and resource use, in Gaza to identify quality gaps and areas for urgent intervention. Methods: As part of a mixed methods study, we used the World Health Organization’s Assessment Instrument for Mental Health Systems Version 2·2 to collect data on mental health services and resources. Data collection was carried out in 2011, based on the year 2010. Results: Gaza’s mental health policy suggests some positive steps toward reform such as supporting deinstitutionalisation of mental health services. The decrease in the number of beds in the psychiatric hospital and the progressive transition of mental healthcare toward more community based care are indicative of deinstitutionalisation. However, mental health legislation in support of deinstitutionalisation in Gaza is lacking. The integration of mental health into primary healthcare and general hospitals has not been fully achieved. Mental health in Gaza is underfunded, human rights protection of service users is absent, and human resources, service user advocacy, and mental health training are limited. Conclusion: Priority needs to be given to human rights protection, mental health training, and investment in human and organisational resources. Legislation is needed to support policy and plan development. The ongoing political conflict and expected increase in need for mental health services demonstrates an urgent response is necessary.